Hledání Nové Evropy v textech T. G. Masaryka a Romana Dmowského : komparativní pohled - Milan Scholz (Studia Historica Brunensia, 2019)
This article provides a comparative analysis of the search for a New Europe in the texts of Tomáš Garrigue Masaryk (1850–1937) and Roman Dmowski (1864–1939). Both Masaryk and Dmowski were prominent representatives of the public and political life in their countries at the end of the 19th and in first decades of the 20th centuries. During the First World War they became the leaders of Czechoslovak and Polish politics in West European exile. Their objectives consisted in the (re-)establishment of independent Czechoslovak and Polish states.